2021
DOI: 10.3389/fphar.2021.638258
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3, Possible Role in Pathogenesis of Periodontal Diseases and Potential Therapeutic Target

Abstract: Periodontal diseases are chronic inflammatory diseases that occur due to the imbalance between microbial communities in the oral cavity and the immune response of the host that lead to destruction of tooth supporting structures and finally to alveolar bone loss. Galectin-3 is a β-galactoside-binding lectin with important roles in numerous biological processes. By direct binding to microbes and modulation of their clearence, Galectin-3 can affect the composition of microbial community in the oral cavity. Galect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 208 publications
(254 reference statements)
0
11
0
Order By: Relevance
“…Despite the bacterial etiology, tissue damage and inflammation are sustained and enhanced by the inflammatory host response with inflammatory mediators such as Galectin-3 (Gal-3), the Nod-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome and Interleukine-1. In particular, Gal-3 is implicated in the regulation of inflammation, as demonstrated in similar disease models [6][7][8].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Despite the bacterial etiology, tissue damage and inflammation are sustained and enhanced by the inflammatory host response with inflammatory mediators such as Galectin-3 (Gal-3), the Nod-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome and Interleukine-1. In particular, Gal-3 is implicated in the regulation of inflammation, as demonstrated in similar disease models [6][7][8].…”
Section: Introductionmentioning
confidence: 77%
“…In bacterial infections, tissue damage and progression of endo-periodontal disease can be determined and sustained by host-released inflammatory mediators. In particular, Gal-3 [6] is implicated in pro-inflammatory In the palatal canal, there was not a predominant taxon. Several anaerobic taxa were identified, such as F. nucleatum (8%), and two species belonging to Porphyromonas spp.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Galectin-3 (Gal-3), which is a 30-kDa lectin secreted mainly by macrophages, contains a carbohydrate-recognition binding domain that binds to β-galactoside ( 16 ). Gal-3 plays an important disease-exacerbating role in autoimmune/inflammatory and malignant diseases ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gal3 has many physiological functions, including adhesion, apoptosis, cell cycle regulation, and cell-to-cell interactions within the extracellular matrix [8][9][10][11]. Moreover, Gal3 has been associated with several diseases, such as cancer, liver diseases, cardiovascular diseases, periodontal diseases, and fibrotic diseases and has even been proposed as a biomarker in several conditions [12][13][14][15][16]. Indeed, we have recently suggested that Gal3 is an attractive molecule to consider in the regulation of the macrophage-related hyperinflammation phase associated withsevere COVID-19 patients [17].…”
Section: Introductionmentioning
confidence: 99%